Design and development of dithienopyrrolobenzothiadiazole (DTPBT)-based rigid conjugated polymers with improved hole mobilities. (21st December 2020) - Bhanvadia, Viraj J.; Machhi, Hiren K.; Soni, Saurabh S.; Zade, Sanjio S.; Patel, Arun L.
Abstract: Donor-acceptor integrated ladder-type dithienopyrrolobenzothiadiazole (DTPBT)-based conjugated building blocks have been used to develop rigid conjugated polymers by copolymerizing them with synthesized ladder-type indoloquinoxaline, π-extended isoindigo and π-extended 2, 1, 3-benzothiadiazole-based conjugated building blocks. Structural aspects of synthesized building blocks are studied by single-crystal X-ray diffraction, which revealed the co-planar structure of indoloquinoxaline-scaffold while twisted but intramolecularly hydrogen-bonded structures of π-extended isoindigo- and 2, 1, 3-benzothiadiazole-scaffolds with number of intermolecular non-bonding interactions. The synthesized DTPBT-based conjugated polymers P-1, P-2 and P-3 are studied for photophysical and electrochemical properties and are found to have moderate to good visible light absorptivity with HOMO energy levels below −5.0 eV. The X-ray diffraction studies indicate strong π−π stacking interactions induced face-on arrangement of polymer chains respective to the substrate. Polymers show π−π stacks promoted high space-charge limited current (SCLC) hole mobilities ranging between 5.6 × 10 −4 –1.3 × 10 −3 cm 2 V −1 s −1 . The obtained SCLC hole mobility data in tandem with the studied structural aspects of monomers and morphological aspects of polymers, suggest that the combination of ladder-type DTPBT-scaffolds (capable of intermolecular π−π interactions) with non-ladder-type planar and structurally rigid π-extended conjugated scaffolds (capable of intermolecular π−π and other non-bonding interactions) is beneficial for getting good hole mobilities. Graphical abstract: Image 1 Highlights: Syntheses of ladder-type and non-ladder-type π-extended conjugated scaffolds. Structural investigation of conjugated scaffolds using X-ray crystal diffraction. H-bonding induced structural rigidity of non-ladder-type conjugated scaffolds. Combining ladder-type–ladder-/non-ladder-type repeating units along polymer chain. Correlating the co-monomer structures with the polymer SCLC hole mobilities.